Pengaruh Media Edukasi Tanda Bahaya Kehamilan “Mattampu” Terhadap Pengetahuan Ibu Hamil - Sharfina Haslin; Agnes Purba (Prodi D III Kebidanan Fakultas Ilmu Kesehatan Universitas Ibrahimy, 2022)
One of the causes of high maternal mortality cases was the low knowledge of pregnant women about the danger signs of pregnancy. Danger signs of pregnancy are signs that experienced by mothers during pregnancy which are used as indicators of complications in pregnancy so that they can detect complications during deliveryThis study aims to assess the influence of the application of educational media on danger signs of pregnancy on the knowledge of pregnant women. This study used quasi-experimental research design with non-equivalent control group pretest and posttest design. The study was conducted in Public Health CenterBojo Baru, Barru district South Sulawesi in August – October 2021. Respondents were divided into 2 groups (26 pregnant women for intervention group and 26 pregnant women for case group). Knowledge value was analyzed using Wilcoxon test and Mann-Whitney test. The results showed that there was a relationship between age and education on level of knowledge of pregnant women about the danger signs of pregnancy. There was an effect of educational media application of pregnancy danger signs on the mother's level of knowledge (p = 0.000 < 0.05). There was a significant difference in level of mother's knowledge between the group that was given the application of educational media on the danger signs of pregnancy and the group that was given education with the MCH handbook (p = 0.000 < 0.05).